Episodic Specificity in Acquiring Thematic Knowledge of Novel Words from Descriptive Episodes - Zhang, Meichao; Chen, Shuang; Wang, Lin; Yang, Xiaohong; Yang, Yufang (Frontiers in Psychology, 2017)
The current study examined the thematic representation of novel words whose meaning was inferred from descriptive episodes. In a lexical decision task, the novel words served as primes, while the corresponding concepts, thematically related words in the same episodes as the learning episodes, thematically related words in a different episode, or unrelated words served as targets. Event related potentials (ERPs) elicited by the targets revealed that relative to the unrelated words, the corresponding concepts and thematic-related words in the same episodes elicited smaller N400s, whereas the thematic-related words in a different episode elicited an enhanced late positive component. A control experiment further showed a priming effect from the corresponding concepts to the thematically related words in the same episode as well as from a different episode, indicating that the absence of a priming effect between the learned novel words and the thematically related words from a different episode was not due to the inappropriate selection of thematically related words in the two conditions. These results indicate that only the corresponding concepts and the thematic-related words within the learning episodes were successfully primed, whereas the thematic associations between the novel words and the thematic-related words from different scenarios were recognized in a late processing stage. Our findings suggest that thematic knowledge of novel words is organized via separate scenarios, which are represented in a clustered manner in the semantic network.